ANALISIS KEPUASAN MASYARAKAT TERHADAP KUALITAS PELAYANAN PUBLIK (Studi di Dinas Kependudukan dan Catatan Sipil Kabupaten Banyumas) - Lynawati Lynawati; Suyudi Suyudi; Suraji Suraji (FEB UNWIKU PURWOKERTO, 2020)
The era of regional autonomy that has been going hand in hand since the new millennium has implications for the demand to improve the quality of public services because one of the mandates of reform is to improve the performance of public services. Idealism to provide excellent quality public services does not seem to be in line with empirical reality. In reality, up to now there are still many citizens who complained about the services provided by the service providers. The purpose of this research is to find out and analyze public satisfaction with public services presented by Dindukcapil, Banyumas Regency. This research was conducted in Dindukcapil Banyumas Regency using survey methods. The object of research is the satisfaction of the service user community. Methods of data collection using questionnaires and documentation. The sampling technique uses accidental sampling. Validity testing uses product moment correlation while reliability testing uses Cronbach's Alpha. Data analysis techniques use Important Performance Analysis (IPA). The results showed that the service user community was satisfied with the public services presented by Dindukcapil Banyumas Regency because the service performance received / felt was higher than its expectation. This is evidenced by the value of each item in the performance attribute which is entirely higher than the value of each item in the expectation attribute. Overall, the percentage ratio of the total score of the performance attributes is also higher than the percentage score of the total expectation attribute, which is 108.9%. Based on these results, the hypothesis which states: